PARTICIPATION OF THE RUSSIAN FEDERATION IN TREATIES ON PRIVATE INTERNATIONAL LAW - Makarov Artem Eduardovich (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This article discusses the types and contents of international treaties to which the Russian Federation is a party, types of agreements are designed to regulate many legal relations in various fields of national and social life involving foreign factors.